Hybrid System Level and Coarse Grid CFD Tool for Three-Dimensional Natural Circulation, Mixing, and Stratification Modeling. (2nd January 2022) - Harvill, R. C.; Lane, J. W.; George, T. L.
Abstract: Natural circulation, mixing, and stratification are important phenomena for the design and safety analysis of many advanced reactor designs with passive safety features as well as large open regions, such as pool reactor designs, spent fuel pools, and containments. Various modeling methods ranging from zero-dimensional (0-D) lumped volumes (or perfect mixing) to full three-dimensional (3-D) computational fluid dynamics (CFD) have been used. Historically, 0-D lumped volume approaches, combined with other modeling methods and assumptions, have been applied to perform so-called conservative analyses, but with the advancement of computational resources and best-estimate-plus-uncertainty methods, it is very desirable to have advanced, multidimensional modeling and simulation capabilities to improve the accuracy of reactor safety analyses, reduce modeling uncertainties, and eliminate the modeling distortions that can occur when simultaneously applying conservatisms. In the past decade there have been large investments in the pursuit of new, higher-fidelity modeling and simulation tools. However, GOTHIC TM, which has been developed and maintained by Zachry Nuclear Engineering (formerly Numerical Applications, Inc.) since the mid-1980s, already provides these capabilities. GOTHIC is an industry-trusted, computationally efficient, coarse-grid multiphase CFD tool that also includes the important attributes of traditional system-level modeling tools, such as component-level models, control system capabilities, and neutron point kinetics models. GOTHIC applies a domain decomposition approach, allowing various levels of fidelity from 0-D to full 3-D to be applied in a single model, giving the user the ability to focus computational resources in the regions of interest while still capturing the integrated system response and important feedback effects. The result is a general-purpose, multiphysics engineering design and analysis tool that can be used for both light water reactor (LWR) and non-LWR designs. This paper provides an overview of 3-D finite volume modeling in GOTHIC, including the governing equations, turbulence model, and solution methods. Additionally, a few of the verification and validation tests from GOTHIC's full test suite are presented to demonstrate fundamental capabilities, including laminar flow in a channel of parallel plates, square and rectangular cavity natural convection, natural convection through vertical and horizontal openings, and natural convection associated with a heated horizontal cylinder in a rectangular cavity. Based on the comparisons with the analytical solutions and experimental results, it is demonstrated that the multidimensional model can perform very well for a wide range of applications.